Development of a Federally Funded Demonstration Colorectal Cancer Screening Program - Janet Royalty, MS; Cynthia Gelb, BS; Marion Nadel, PhD; A. Blythe Ryerson, MPH; Anne Major, BA; Eddie Reed, MD; Laura C. Seeff, MD; Amy DeGroff, MPH; Florence Tangka, PhD; Ena Wanliss, MS (Centers for Disease Control and Prevention, 2008)
Colorectal cancer is the second leading cause of cancer-related mortality among U.S. adults. In 2004, treatment costs for colorectal cancer were $8.4 billion.There is substantial evidence that colorectal cancer incidence and mortality are reduced with regular screening. The natural history of this disease is also well described: most colorectal cancers develop slowly from preexisting polyps. This slow development provides an opportunity to intervene with screening tests, which can either prevent colorectal cancer through the removal of polyps or detect it at an early stage. However, much less is known about how best to implement an effective colorectal cancer screening program. Screening rates are low, and uninsured persons, low-income persons, and persons who have not visited a physician within a year are least likely to be screened.Although the Centers for Disease Control and Prevention (CDC) has 15 years of experience supporting the National Breast and Cervical Cancer Early Detection Program for the underserved population, a similar national program for colorectal cancer is not in place. To explore the feasibility of implementing a national program for the underserved U.S. population and to learn which settings and which program models are most viable and cost-effective, CDC began a 3-year colorectal cancer screening demonstration program in 2005.This article describes briefly this demonstration program and the process CDC used to design it and to select program sites. The multiple-methods evaluation now under way to assess the program's feasibility and describe key outcomes is also detailed. Evaluation results will be used to inform future activities related to organized screening for colorectal cancer.